PEMBAGIAN HARTA WARISAN TERHADAP ANAK ANGKAT MENURUT HUKUM ADAT BATAK DI DESA TOLANG JULU KECAMATAN SAYUR MATINGGI - Muhammad Risnawan Nasution (UM.Tapanuli Selatan, 2024)
A person's hope to have descendants is not always fulfilled; there are many people who do not have children and then adopt someone else's child to become the successor of their family. In customary law, child adoption is a cash transaction; the child is released from the old environment simultaneously with the payment of compensation in the form of a magical object, and after the payment, the child enters the family environment as a child. The research method used is Empirical Juridical research. Based on the research findings, the process of child adoption according to Batak customary law in Tolang Julu Village, Sayur Matinggi District, is carried out in several stages, starting from Consensus or Deliberation (Pasada Tahi) to the child handover ceremony. Meanwhile, the position of the adopted child in the distribution of inheritance according to Batak customary law in Tolang Julu Village, Sayur Matinggi District, is recognized as equal to that of a biological child. With the recognition of the adopted child's position as equal to that of a biological child, the adopted child holds the same status as a biological child, thus the adopted male child is entitled to inherit from the adoptive parents.